Risk Assessment of Distributed Network Data Security Based on SimHash Algorithm - Tang, Yanbin (International Journal of Industrial Engineering: Theory, Applications and Practice, 2024)
Distributed network data has the characteristics of distribution and concurrency, which leads to the complexity of data processing and reduces the effectiveness of security risk assessment. Therefore, a security risk assessment method for distributed network data based on the SimHash algorithm is proposed. The actual support of the distributed network data set is reconstructed by probability distortion technology, and the data mining results after probability transformation are obtained by using the data mining method of random disturbance. In order to avoid the existence of duplicate information and redundant data, duplicate distributed network data is removed by calculating text similarity. Finally, the SimHash algorithm is used to calculate the hash value before and after the distributed network data attack, calculate the security risk assessment value of the distributed network data, and complete the security risk assessment. The analysis of the experimental results shows that the proposed method effectively improves the reliability of risk assessment of distributed network data and reduces the communication overhead of the assessment, with the maximum communication overhead not exceeding 10 bits. Therefore, the research method has high effectiveness and practicability.